"A splendid norm": Human Plants and the Eugenic Secular, 1906–1926. (18th April 2022) - McCrary, Charles
Abstract: This article analyzes eugenics and the secular in early twentieth-century California through the career of Luther Burbank. Burbank was a famous plant breeder who cultivated a theory of human progress based on his breeding work. For him, humans were part of an always-evolving and immanently spiritual natural world. And it was the task of civilized people to perfect that world, making it more beautiful and more productive. This project rested on an enchanted secularization narrative in which the wondrous natural world is made better through human direction. Late in his life, in the 1920s, Burbank turned his attention to fundamentalists and their "primitive" and "superstitious" beliefs about evolution. With attention to the aesthetics of the secular, this article analyzes secularism as a biopolitical project that racializes religion and its others. In Burbank's case, this project is the result of a liberal romanticism that sought to unite spirituality and science.